إسهامات الفلاسفة المسلمين في الفكر الإنساني - عبد القادر هبيد. فتحي محمد (Aljameai, 2025)
المستخلص: استهدف البحث إبراز إسهامات الفلاسفة المسلمين في الفكر الإنساني، مع التركيز على مشروع ابن رشد بوصفه نموذجًا بارزًا للتوفيق بين التأويل العقلي للنصوص الدينية ومتطلبات البرهان الفلسفي. وقد انطلق البحث من تساؤلات مركزية حول دور الفلسفة الإسلامية في نقل وتطوير التراث العقلي، وكيف انعكس مشروع ابن رشد على الفكر الإسلامي والأوروبي، مع السعي لاستخلاص دلالات حضارية يمكن الإفادة منها في الواقع المعاصر. وأظهرت النتائج أنّ الفلسفة الإسلامية لم تكن مجرّد وسيط ناقل للفكر اليوناني، بل أضافت إليه أبعادًا جديدة تنسجم مع مقاصد الشريعة الإسلامية. وقد برز ابن رشد في صياغة مشروع فكري مستقل يقوم على اعتماد البرهان العقلي لتأويل النصوص الشرعية، مما أتاح تأسيس رؤية متوازنة تجمع بين الحكمة والشريعة. كما أثبت البحث أنّ الرشدية اللاتينية مثّلت جسرًا بين الفلسفة الإسلامية والفكر الأوروبي الوسيط، وأسهمت في نشأة النزعة العقلانية والنقدية التي مهدت للتنوير. وأوصى البحث بضرورة إعادة قراءة التراث الفلسفي الإسلامي بعين نقدية معاصرة، وإدماج الفكر الرشدي في المناهج الدراسية لما يحمله من نموذج متوازن بين العقل والدين، إضافة إلى دعم حركة الترجمة والتعريف بفكر الفلاسفة المسلمين في الأوساط الأكاديمية العالمية، بما يعزز الحوار الحضاري ويؤكد على إسهام الفلسفة الإسلامية في إثراء الفكر الإنساني. Summary: This study aims to highlight the contributions of Muslim philosophers to human thought, with a special focus on Ibn Rushd as a key figure who sought to reconcile rational interpretation of religious texts with the requirements of philosophical reasoning. The research addresses central questions concerning the role of Islamic philosophy in transmitting and developing intellectual heritage, the impact of Ibn Rushd’s project on both Islamic and European thought, and the civilizational lessons that can be drawn for the contemporary context.The findings reveal that Islamic philosophy was not merely a channel for Greek thought but enriched it with new dimensions aligned with the objectives of Islamic law. Ibn Rushd emerged as an independent thinker who grounded religious interpretation in demonstrative reasoning, creating a balanced vision between philosophy and Sharia. The study also showed that Latin Averroism acted as an intellectual bridge between Islamic philosophy and medieval European thought, contributing significantly to the rise of rationalism and critical philosophy that paved the way for the Enlightenment.The research recommends re-examining Islamic philosophical heritage through a contemporary critical lens, integrating Ibn Rushd’s thought into academic curricula as a model of harmony between faith and reason, and supporting translation projects to introduce Muslim philosophers’ contributions to global scholarship, thus fostering intercultural dialogue and reaffirming the vital role of Islamic philosophy in enriching